“Elaboracion de jamonada utilizando mezclas de carnes rojas (vacuno y cerdo) y pescado gamitana ( colossoma macropomum)” - Ramírez Navarro,Manuel (1996)
The present study is based on the need for new consumption habits of the population of the Region of San Martin, using as the Gamitana living aquatic species in the production of sausages with mixtures of meat (beef and pork) red. Technological tests are developed characterizing the raw and trials of formulation with levels of replacement to 30%, 40% and 50% of Gamitana meat in the mixture, which was evaluated by its chemical characteristics (protein, fat, moisture) and sensory analysis; determining the optimal level of substitution of 40% Gamitana, representing the following formula:-20.92% Gamitana meat. -15.69% meat of beef. -15.69% pork meat. -18.03% fat of pork, etc. Mix that it was subjected to three hours of cooking at 85 ° C for the production of sausages. The study of stability of the product 5 ° C, or ° C and - 10 ° C for 60 days, indicates a slight variation in the levels of acidity and peroxide, iodine, atribuid...